(untitled) (Research, Society and Development, 2021)
The triumph of the crops association with vegetables in semi-arid environment depends on crop types grown and adequate manipulation of treatment-factors tested such as fertilization, plant population, among others. Thus, this investigation aimed to valuate the bio-economic return of beet-rocket strip-intercropping in diverse balanced quantities of hairy woodrose (M. aegyptia) and roostertree (C. procera) biomass (20, 35, 50 and 65 t ha-1 on base dry) and in different rocket plant population (40, 60, 80 and 100% of that recommended population in monocropping - RPM), associated with the beet population of 100% of the RPM, in two years of cultivation. The bio-economic indices: land equivalent ratio (LER), intercropping advantage (IA), actual yield loss (AYL), productive efficiency index (PEI), canonical variable score (Z), gross return (GR) and net return (NR), rate of return (RR) and profit margin (PM) were assessed. The greatest bio-economic returns of beet-rocket strip-intercropping were of: 1.87; 7.44; 1.90; 0.98; 2.52; 85,827.79 and 65,425.01 R ha-1; 4.24 R for each real invested, and 77.02%, respectively, for LER, IA, AYL, PEI, Z, GR, NR, RR and PM in the biomass quantity of 65 t ha-1 of hairy woodrose and roostertree, in the rocket population of 100% of the RPM (a million plants ha-1). The hairy woodrose and roostertree biomass use from Caatinga biome proved to be a viable technology for growers who practice the cultivation of beet-rocket strip-intercropping in semi-arid environment.